Assessing and Teaching Reading to Pupils with Reading Disabilities in Nyeri and Nairobi Districts-Kenya: The Teachers’ Opinion - Runo, Mary; Kargu, Geoffrey; Mugo, John K. (Journal of the American Academy of Special Education Professionals, 2010)
The study aimed at finding out whether teachers can identify the courses of reading disabilities in learners. It intended to establish whether teachers have adequate knowledge of identifying learners with reading disabilities, determine the proportion of non-readers in grade five. It also investigated the existing methods and materials teachers use in teaching and remediating reading including the difficulties teachers encounter when teaching. Finally, the study aimed at finding out whether there are any gender differences in learners with reading disabilities. This study adopted both qualitative and quantitative research approaches where mixed method designs were used for collecting and analyzing data for both teachers and learners. The study embarked on interviews for learners by use of structured questionnaires. Learners were also assessed to determine the level of reading ability. The study also used semi-structured questionnaires for teachers. A focus group interview was also held with teachers in the study. The study was conducted in Central and Nairobi provinces where Nyeri and Nairobi districts respectively were used. Purposive sampling was used to select the provinces, districts, divisions, primary schools, populations and the target groups, in this case of the teachers and learners. This was based on KCPE results analysis for 2006, the division that performed best overall in Nairobi and the poorest performing division in Nairobi from KCPE results, 2006. Nyeri District was representative of rural primary schools and therefore, the municipality and one rural division was selected. In this case, Nyeri municipality division and Othaya division. There were four schools selected from each of the four divisions, giving a total of 16 schools from both Nairobi and Nyeri. In each school, 15 pupils were purposively selected from the list of those learners scoring 250 marks and below from their end of standard 5 examinations. If the learners were more than 15 scoring 250 marks and below, the researcher used random sampling. A total of 240 learners were the sample for the study, streams were not considered in the study. All teachers who taught English to the learners in the study, in class in 2007, were in the study. All the class teachers of grade five in 2007 of not the English teacher were also included in the study. A total of 34 teachers participated in the study. There were five types of instruments namely: questionnaires for teachers, questionnaires for learners, assessment tools for reading--wood list A to E, passage 1 to 4; checklist on reading errors and learners’ reading attitude survey. Statistical Package for Social Sciences (SPSS) was used to analyze quantitative data from the assessment tools, questionnaires for learners, and reading attitude survey. All the hypotheses were tested at P=0.05 Pearson product moment correlation coefficient was used to measure the strength and direction of the relationship between the different variables. Multiple regression analysis and chisquare test were also used. Teachers’ questionnaire was analyzed through descriptive research. The following results were obtained based on the objectives, questions and hypotheses of the study: The teachers assessed their learners reading ability but they did not use proper methods of assessment; teachers were able to identify children who could not read at class level as non-performers but not able to identify the specific reading difficulties. Non-readers ranged from 0 to 27.1% for Nairobi and 0 to 53.6% in Nyeri; almost half of the teachers in the study did not either teach reading or they did not know the methods to use in teaching reading. The study indicated that there were more boys (103) than girls (78) who could not read. The study concluded that: teacher training syllabus on reading whether in mother tongue, Kiswahili or English be adequately developed to cater for individual learners and equip the teachers with methods for teaching reading adequately. More time be given to teaching reading, assessing reading and remediating reading disabilities both at the primary teacher education colleges and at primary schools; reading in an ongoing process and therefore it is recommended that reading be taught all through primary levels. (standard 1 to 8) and be within the developmental states of reading; reading readiness curriculum be developed for early childhood and at primary levels. Such policy should ensure smooth transition of learners’ movement from home, preschool and primary schools. Finally the study recommended adequate development of teacher training syllabus on reading in mother tongue English or Kiswahili more time, reading be taught continuously from standard 1 to 8 and smooth transition for learners’ movement from home, pre-school and primary schools.